Barriers to provision of high quality care for patients with end stage heart failure. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Mair, Frances; Brown, Susan; Morrison, Deborah; Macleod, Una; May, Carl
Abstract : Background: It is known that those with end stage heart failure (ESHF) experience symptoms that have a negative impact on their daily lives and that they feel unsupported. Aims: The present study aims to identify barriers to provision of high quality care for those with ESHF. Methods: Semistructured interviews with patients and close persons with ESHF (26 patients; 18 close persons). Qualitative data analysed using thematic analysis but informed by Normalisation Process Theory. Inclusion criteria: grade 3 or 4 NYHA classification heart failure, with ongoing symptoms despite optimal therapy, and a history of admissions or multiple health professional contacts for heart failure. Results: Polypharmacy makes adherence difficult and is perceived as a precipitant of admissions. This is exacerbated by the fact that patients are dispensed ever changing brands of different coloured tablets, which makes adherence challenging. Multiple appointments at different clinics (for both cardiac and non-cardiac problems) on different days pose major difficulties for patients, both from the logistical perspective (eg, organising transportation) but also physically, as attendance at these appointments can be exhausting. Lack of continuity of care and poor communication between professionals and professionals and patients also presents difficulties. Information is often not communicated to patients in ways that they find coherent. Importantly, participants are usually unable to identify suitable emergency care plans that could help them when they experience deteriorations in their condition. Conclusions: Uncoordinated care, multiple appointments and polypharmacy are major problems and there is clear potential for rationalisation of therapeutic regimens and systems for follow up. Those with ESHF need clear pathways/plans regarding what to do in an emergency and need access to services to help them action such plans. More counselling services are needed to help support these individuals who have a range of support needs, particularly as they transition from chronic disease management to palliative care.